Intra-arterial administration of tumor-targeting Salmonella typhimurium A1-R regresses a cisplatin-resistant relapsed osteosarcoma in a patient-derived orthotopic xenograft (PDOX) mouse model. Issue 12 (18th June 2017) - Igarashi, Kentaro; Kawaguchi, Kei; Murakami, Takashi; Kiyuna, Tasuku; Miyake, Kentaro; Nelson, Scott D.; Dry, Sarah M.; Li, Yunfeng; Yanagawa, Jane; Russell, Tara A.; Singh, Arun S.; Yamamoto, Norio; et al.
ABSTRACT: Previously, a patient-derived orthotopic xenograft (PDOX) model was established with a lung metastasis from an osteosarcoma patient which developed after adjuvant cisplatinum (CDDP) treatment. In this model, we previously demonstrated the efficacy of trabectedin (TRAB) and temozolomide (TEM) compared with CDDP. In the present report, osteosarcoma tissue was implanted orthotopically in the distal femur of mice which were randomized into the following groups when tumor volume reached approximately 100 mm 3 ; On day 14 after initiation of treatment, all but CDDP significantly inhibited tumor volume growth compared with untreated controls. Control (G1): 793.7 ± 215.0 mm 3 ; CDDP (G2): 588.1 ± 176.9 mm 3 ; Salmonella typhimurium A1-R ( S. typhimurium A1-R) intravenous (i.v.) (G3): 269.7 ± 72.7 mm 3 ; S. typhimurium A1-R intra-arterial (i.a.) (G4): 70.2 ± 18.9 mm 3 (CDDP: p = 0.056; S. typhimurium A1-R i.v.: p = 0.0001; S. typhimurium A1-R i.a.: p = 0.00003, all vs. untreated controls). i.a. administration of S. typhimurium A1-R was significantly more effective than either CDDP (p = 0.00007), or i.v. administration of S. typhimurium A1-R (p = 0.00007) and significantly regressed the tumor volume compared with day 0 (p = 0.001). The new model of i.a. administration of S. typhimurium A1-R has great promise for the treatment of recalcitrant osteosarcoma.